R. I. HOROBETS: COMMUNICATIVE-PRAGMATIC SPECIFICITY OF FUNCTIONING OF SINGLE-COMPOUND SENTENCES-PERSONAL SENTENCES IN THE LANGUAGE OF MODERN UKRAINIAN PROSE FOR CHILDREN - HOROBETS. , R. I. (Linguistic Bulletin (Movoznavchyi Visnyk), 2021)
Summary. Introduction. In modern linguistics, a lot of scientific research is devoted to the analysis of the functioning of simple structures in literary texts.However, a study of the communicative and pragmatic potential of single-syllable sentences, which would be based on artistic texts for children, has not yet been carried out.Purpose. Analysis of structural-semantic and communicative-pragmatic features of functioning of one-syllable definite-personal sentences in the language of modern Ukrainian prose for children, establishment of regularities of their distribution and actualization.Results. One-syllable definite-personal constructions constitute a syntactic category peculiar to structure and semantics. They are characterized by the transfer of emphasis from the actor to the action, the injection of action, especially when the verb is in the imperative form. Modern Ukrainian prose for children demonstrates the process of actualization of definite-personal sentences, which reveal different communicative-pragmatic specifics of functioning, which depends on the subject of the work, its genre variety, as well as on the personal preferences and intentions of the writer.Originality. Scientific research is the first attempt to analyze the communicative-pragmatic specifics of the functioning of one-syllable definite-personal sentences in the language of modern Ukrainian prose for children.Conclusion. With the help of researched syntactic units the author of the work of art reveals the individualized inner world of the hero, brings it to the center of the image, dynamizes the speech of the characters, conveys the emotionally expressive and intonational nature of expression, saves expressive means, promotes stylization.We see the prospect of further scientific research in the analysis of formal-syntactic and functional-stylistic features of other types of one-syllable sentences in the language of modern Ukrainian prose for children.